Optimization of protoplast fusion conditions of vetiver grass (Vetiveria zizanioides) - Leaungthitikanchana, Sumana; Thongdonyod, Khachapohn (YRU Journal of Science and Technology, 2020)
Vetiver (Vetiveria zizanioides) belongs to Poaceae family which is used for soil and water conservation. The improvement of this grass through the conventional breeding is very limited due to male sterility. Protoplast fusion technology is a useful technique that can be solved this limitation in vetiver improvement. Therefore, this study aimed to optimize the protoplast fusion conditions for somatic hybridization between two vetiver grass varieties, including Kamphaeng Phet 2 (Vetiveria zizanioides Nash) and Prachuap Khiri Khan (Vetiveria nemoralis A. Camus) by polyethylene glycol (PEG)-mediated method. The mesophyll protoplasts of both varieties were incubated with various combination between concentrations of PEG 6000 (10, 20 or 30%) and incubation periods (10, 20 or 30 min). The experimental design is 4×3 completely randomized factorial design (4×3 factorial in CRD) with 3 replications. The results showed that the highest percentage of binary fusion (43.45%) and the viability of protoplasts (89.63%) were obtained from 10% PEG 6000 with 30 min incubation period. This research is the preliminary study which is useful to produce somatic hybridization for vetiver improvement in the future.